Optimization of Concrete Mix Design Using Statistical Methods - Purnima (My University, 2018)
Concrete is the most essential part of the civil engineering projects. Optimization of the concrete mix design is motivated by the ever- increasing need of the designers to proportion the concrete mixtures that are able to satisfy the multiple performance necessities. Purpose of the current work is to develop a model that is capable of reproducing a concrete strength between 60MPa to 90MPa within a specific range of cement content, fly ash content, silica fume content and cost. The model can generate data on mix proportions and their corresponding compressive strength and slump, thereby, providing useful information safe and ready-to-use mix designs. 21 mixes of strengths 60MPa, 65MPa…..90MPa and 3 required slumps i.e. 50mm, 80mm and 120mm were designed and casted (100x100x100 mm cubes) with 4 replicas of each. Regression analysis was carried out on the experimental data and mathematical equations for strength and slump were developed. The two equations so developed along with 11 other constraints were then used to develop a optimization model using MATLAB optimization tool.
Keywords: OPTIMIZATION; CONCRETE MIX DESIGN; MATLAB; REGRESSION ANALYSIS; MATHEMATICAL EQUATIONS